Kualitas Layanan Mall Pelayanan Publik Dalam Mendukung Smart Governance Serta Keterbukaan Informasi - Ramdani, Faisal Tri; Feriandy; Didik Kristyanto; Djoko Tjahyono; Andriansyah , Andriansyah; Izzatusholekha, Izzatusholekha (JURNAL KOMUNIKATIO, 2025)
Public service is the responsibility that the government must carry out to meet the needs of community services. One form of fulfilling the needs of public services carried out by the government is to innovate services through the Public Service Mall (MPP). The implementations of this program is carried out by the East Lombok Regency Government which already has an MPP and has been implemented to carry out services for the community. This study aims to analyze the quality of MPP services in East Lombok Regency in supporting innovative governance and openness of information to provide maximum service to the community. This study uses a descriptive quantitative method with a purposive sampling technique and sample calculations using the Slovin formula. The calculation of the results of the respondent's calculations using WMS with a variable focus based on the theory of service quality Zeithaml, Parasuarman & Berry and the Smart City Theory Smart City (Giffinger et al. 2007) with the dimension of innovative governance in supporting openness of information. From the results of the recapitulation of the assessment of the quality of service and the implementation of innovative governance, the calculation results were 3.89 with a suitable category; this shows that the quality of MPP services in East Lombok Regency has been running well and supports openness of information for the public. But in its implementation there must always be an increase in services so that the existence of MPP can provide maximum service to the public and realize innovative governance towards a smart city in East Lombok Regency.